Islam in the Contemporary World - Lina Pusvisasari; Alma Nur Marsya Ma’rif; Siti Rahap Rahmawati; Siti Hopipah (Penerbit Hellow Pustaka, 2025)
Islam is a broad and comprehensive religion that continues to evolve to meet the demands of the modern world. Muslims today face new challenges and opportunities in a society shaped by technology, global relations, and diversity. This journal examines how Islam, which represents a collection of ideas and ways of life, addresses contemporary issues such as democracy, human rights, gender equality, the environment, and technological advancement. With a comprehensive analytical approach, this study shows how Islam is flexible and remains key in overcoming modern problems while maintaining its basic principles. The integration of Islamic principles with the demands of the modern world is highly dependent on the concepts of ijtihad, maqasid sharia, and wasathiyyah (moderation). The results of this study indicate the need for a new interpretation of modern Islam that continues to respect its basic values, as well as the need for dialogue between tradition and contemporary society to create a progressive and inclusive Islamic society.